Discussion and Study of Design on Modification Coefficient and Helix Angle of Gear of Tube Mill - Ben Daochun; Wang Dongsheng; Wang Fuguang; Li Xiaoping; Zha Wenwei (Jixie chuandong)
From the analysis of design on modification coefficient and helix angle of gear of tube mill,the new design concept of small displacement,low slip ratio difference and the small helix angle is elaborated. The allocation method and precautions of helix angle selection on total modification coefficient for gearare described.Through the analysis calculation and comparison with practice,it concluded that the value of optimizing of distribution on total variation coefficient can be obtained based on the calculation by computer program. Not only the slip rate differential Δη is very low and the sliding wear is reduced,but also has a higher degree of coincidence and the contact stress is low which can satisfy 0 < x < 1,thus the manufacturing cost can be reduced. At the same time,the small helix angle（ 2° 4°） for gears of tube mill can be contribute to improve carrying capacity of gear and not produce excessive large axial force.